Gambaran pengetahuan, sikap, dan tindakan peserta Prolanis hipertensi tentang penyakit hipertensi di tempat praktik dokter mandiri Kota Manado - Bryan Michael Andreas Pasla; Margareth Rosalinda Sapulete; Iyone Esra Tiurma Siagian (Jurnal Kedokteran Komunitas dan Tropik, 2026)
Background: Hypertension is one of the many health problems commonly found in adults, characterized by increased blood pressure. If not properly managed, it can lead to complications such as stroke, heart attack, or kidney failure. In Indonesia, with the Chronic Disease Management Program (Prolanis) and its activities and programs, it is necessary to provide an overview of knowledge, attitudes, and practices regarding hypertension. Aim: To find out the description of knowledge, attitudes and actions of participants in the chronic hypertension disease management program at the independent doctors’ practices in Manado City. Methods: This study employed a quantitative descriptive approach with a cross-sectional design. The sampling technique used total sampling and a questionnaire as the research instrument. The study was conducted from September to November 2025. Results: The level of knowledge of respondents in the good category was 73.1%, the sufficient category was 26.9%, and the level of attitude of respondents in the good category was 88.2%, the sufficient category was 11.8%, and the level of action in the good category was 70.6%, the sufficient category was 28.6%, and the less category was 0.8%. Conclusion: The level of knowledge, attitudes, and actions of Prolanis hypertension participants regarding hypertension at independent doctor practices in Manado city is considered to be good.